Very brief on quantum computing with special respect to ion traps technology - Simonović, Svetomir (Advanced Technologies and Materials, 2021)
Because of the continuing miniaturization of integrated circuits it appears that quantum phenomena will play a more and more dominant role in their design and functioning. Therefore, the work exposes concise quantum mechanical and mathematical background of quantum phenomena based computing through the introduction of concepts such as Hilbert space, qubit, Bloch sphere, quantum gate and measurement. Recent improvements in ion- trap technology based computing suggest ion- trap technology as the most promising one for use in quantum computing. So, the paper describes the ion- trap based technology, its use in quantum computation and its latest applications in quantum computing. It turns out that recent ion- trap technology based computers dramatically improves on all of the Vincenzo’s criterions.